The prevalence and the causes of minimal intestinal lesions in patients complaining of symptoms suggestive of enteropathy: a follow-up study. Issue 10 (15th August 2008) - Biagi, F; Bianchi, P I; Campanella, J; Badulli, C; Martinetti, M; Klersy, C; Alvisi, C; Luinetti, O; Corazza, G R
Abstract : Aims: Although they are non-specific, minimal intestinal lesions are at the end of the coeliac histological damage spectrum. To investigate whether minimal intestinal lesions in patients without endomysial antibodies are due to coeliac disease, their prevalence, causes and risk of evolving into frank coeliac disease were studied. Methods: From January 2000 to December 2005, 645 duodenal biopsies were performed. In 209 patients, duodenal biopsies were performed independently of endomysial antibody results. Clinical data and HLA-typing of all the patients negative to endomysial antibodies but with minimal mucosal lesions were re-evaluated. Three years later, they were offered to be seen again, and further investigations were proposed. Results: 14 out of 209 patients had minimal mucosal lesions and negative endomysial antibodies. Two patients were lost to follow-up; in 7/12 patients, symptoms and histological lesions were due to a different condition, not related to coeliac disease. In 11/12 patients, HLA-typing made diagnosis of coeliac disease very unlikely. Only one patient was on a gluten-free diet because of gluten-sensitive symptoms and was DQ2 + /DQ8 + . Conclusions: Minimal duodenal lesions in patients negative to endomysial antibodies are rare and are likely to be due to conditions unrelated to coeliac disease.